Low power, area efficient, and temperature-variation tolerant bidirectional current source for sensor applications. (March 2016) - Gilda, Neena A.; Hande, Vinayak G.; Sharma, D.K.; Rao, V. Ramgopal; Baghini, Maryam Shojaei
Abstract: This paper presents a novel temperature invariant, low power, and area efficient bidirectional current source. The current source can be used as an analog front end R–V converter for different types of resistive sensor applications. The current source is based on weighted sum of thermal voltages and difference of threshold voltages. High V TH transistors operating in sub-threshold region along with regular V TH transistors in strong inversion region form a temperature invariant current source. A current switching technique is presented in this paper for producing a periodic bidirectional current source, fabricated in 180 nm CMOS technology for low cost sensor applications. The maximum total current variation simulated is 13 nA (±0.5%) for typical value of ±715 nA reference current over the temperature range of 25–125 °C. The fabricated test circuit lies in SNFP corner and shows ±1% variation in positive and ±1.67% variation over the temperature range of 25–125 °C. Total area consumed by the circuit is 100 µm×35 µm. The behavior of the bidirectional current source has been tested using a piezo-resistive cantilever based explosive detector sensor, with 20 ppb TNT vapor concentration and 10 parts per billion resolutions with sensitivity of 10 µV/ppb.